Teacher Supply and Demand: Surprises from Primary Research - Wayne, Andrew J. (Education Policy Analysis Archives, 2000)
An investigation of primary research studies on public school teacher supply and demand revealed four surprises. Projections show that enrollments are leveling off. Relatedly, annual hiring increases should be only about two or three percent over the next few years. Results from studies of teacher attrition also yield unexpected results. Excluding retirements, only about one in 20 teachers leaves each year, and the novice teachers who quit mainly cite personal and family reasons, not job dissatisfaction. Each of these findings broadens policy makers' options for teacher supply.